2015
DOI: 10.1016/j.soildyn.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of seismic response of cantilever retaining walls: Limit analysis vs shaking table testing

Abstract: a b s t r a c tThe earthquake response of cantilever retaining walls is explored by means of theoretical analyses and shaking table testing conducted at University of Bristol (EERC -EQUALS). The theoretical investigations employ both limit analysis and wave-propagation methods, which take into account different aspects of the problem such as inertia, strength, kinematics and compatibility of deformations. The experimental programme encompasses different combinations of retaining wall geometries, soil configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 32 publications
(47 reference statements)
2
20
1
Order By: Relevance
“…Thus, an active state is not developed behind the stem despite the fact that the acceleration is applied toward the backfill soil, and, consequently, the retaining wall moves away from the backfill soil. The present study observations are also in contrast with what was observed for the behavior of a cantilever-type retaining wall modeled via a numerical model by Green et al (2008) and via an experimental work by Kloukinas et al (2015)-both of these studies reported that a maximum value of P stem is same to what is observed for a rigid retaining wall. Fig.…”
Section: Seismic Earth Pressure Forces: P Stem and P Vpcontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, an active state is not developed behind the stem despite the fact that the acceleration is applied toward the backfill soil, and, consequently, the retaining wall moves away from the backfill soil. The present study observations are also in contrast with what was observed for the behavior of a cantilever-type retaining wall modeled via a numerical model by Green et al (2008) and via an experimental work by Kloukinas et al (2015)-both of these studies reported that a maximum value of P stem is same to what is observed for a rigid retaining wall. Fig.…”
Section: Seismic Earth Pressure Forces: P Stem and P Vpcontrasting
confidence: 99%
“…Notionally, the vertical seismic acceleration may contribute to the vertical seismic inertia and, as a consequence, may slightly affect the performance response of the cantilever-type retaining wall. However, arguments of several past studies (like Green et al 2008;Cakir 2013;Kloukinas et al 2015;and Jo et al 2017) as well as that of Bakr and Ahmad (2018a) suggest that it is primarily the horizontal seismic acceleration that contributes to the seismic earth pressure force and affects the stability of a retaining wall. The same has been observed through the results of the present study as well as shown later in the results section of this paper.…”
Section: Seismic Loadingmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was presented in the following sequence. First, the finite element model developed was verified by experimental findings of physical models [28], and the results were also compared and validated with results of published numerical studies. Then two series of analysis were carried out.…”
Section: Introductionmentioning
confidence: 97%